Histologia do fígado de tilápia do Nilo (Oreochromis niloticus) alimentados com dietas contendo silagem biológica de pescado - Honorato, Claucia A.; Cruz, Claudinei da; Carneiro, Dalton J. [UNESP]; Machado, Marcia R. F. [UNESP]; Nascimento, Camila A.; Saturnino, Klaus C. (Revista Pesquisa Veterinaria Brasileira, 2014)
This study aimed to evaluate possible histopathological liver of tilapia fed diets containing fish silage and level protein. Sample of 180 fed with tilapia fingerlings fed with diets containing three protein levels (20, 24 and 28% CP), and Proportions residue fermented silage of tilapia (1/4 and 1/2) of were analyzed during 75 days. The tissue fragments were fixed in Bouin and included in Histosec (R). After that, between 2 to 5 mu m slices were done in a rotation microtome. The methods used for tissue analysis were hematoxilin/eosin and PAS. The histological slices were examined under light microscope (Olympus BX-50). The disarray in the morphology of the liver of fish fed biological silage was influenced by high protein levels, and increased proportions of 1/2 of animal protein diets. It was observed that the variation of hepatocytes is directly related to the type of diet for fish. In fish fed diets containing 28% CP, the liver showed disruption of the structure cordon of hepatocytes, necrosis and shifting points of the core to the periphery. Elevated levels of biological fish silage cause deleterious changes in the liver. The level of protein required to maintain the health of the associated development fish is 24% crude protein.

Este estudo teve como objetivo avaliar as possíveis alterações histopatológicas hepática de tilápias do Nilo alimentadas com dietas contendo silagem biológica de pescado com diferentes concentrações protéicas. Foram utilizados 180 juvenis alimentados com dietas contendo três níveis de proteína (20, 24 and 28% PB), e duas proporções de silagem biológica (¼ e ½) durante 75 dias. Os fragementos de fígado foram fixados em Bouin e inclusos em Histosec®. Posteriorente foram cortados em microtomo com espessura de 2 a 5μm. O método utilizado para coloração foi hematoxilina/eosina e PAS. Os cortes histológicos foram analisados em microscopio de luz. O desarranjo na morfologia do fígado dos peixes alimentados com silagem biológica foi influenciado pelos altos níveis protéicos, e pelo aumento ½ de proporções de proteínas de origem animal das dietas. Foi observado que a variação dos hepatócitos está diretamente ligada com o tipo da dieta fornecida para os peixes. Nos peixes alimentados com as dietas contendo 28% PB, o fígado apresentou desarranjo da estrutura cordonal dos hepatócitos, pontos de necrose e deslocamento do núcleo para periferia. Níveis elevados de silagem biológica de pescado provoca alterações deletérias no fígado. O nível de proteína adequado para manter o desenvolvimento associado à saúde do peixe é de 24%PB.
Histology liver in Nile tilapia (Oreochromis niloticus) fed diets with fish silage
Keywords: Nile tilapia; Oreochromis niloticus; Liver histology; Fish silage; Hepatocytes; Tilápia do Nilo; Oreochromis niloticus; Histologia do fígado; Silagem biológica de peixe; Hepatócitos